PROGRESSIVE RELAXATION BERPENGARUH TERHADAP PERUBAHAN TEKANAN DARAH LANJUT USIA HIPERTENSI DIKELURAHAN TANGKERANG TENGAH - Isna Ovari; Silvia Nora Anggreini; Moh Hamdan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: The second most common disease experienced by patients in Riau Province is hypertension with 2,160,932 people, the highest prevalence in Riau is Pekanbaru, as many as 422,443 people (Dinkes Riau, 2020). If someone who has hypertension does not get treatment and control regularly, it will bring the patient into more serious cases and can even cause death (Nurul, 2020). Efforts to prevent complications in hypertension need to be carried out with proper hypertension management, one of which is non-pharmacological management. One of the non-pharmacological management is relaxation techniques, including progressive relaxation. This study aims to determine the effect of progressive relaxation on changes in blood pressure in the elderly with hypertension in RW 08 Tangkerang Tengah Village, this study was carried out on 16 May to 10 June 2021. The design of this study used a pre-experimental design with a one group pre-post test design. . The number of samples was 15 hypertension patients in RW 08 using purposive sampling technique. The results showed that the average difference in systolic blood pressure before and after progressive relaxation was 7,133 and the average diastolic difference before and after being given progressive relaxation was 7,200. There is a significant difference before and after progressive relaxation on changes in blood pressure in the elderly where the p value (0.000) means that there is an effect of progressive relaxation on changes in blood pressure in the elderly in RW 08 Tangkerang Tengah Village. The recommendation from this research is for nurses to do progressive relaxation to reduce blood pressure in hypertensive patients, as well as input in the selection of nursing interventions.Keywords: Hypertension, Progressive relaxation, Elderly